O uso de técnicas de Gestão de Processos de Negócio (BPM), linguagem simples e direito visual para melhoria do entendimento de editais. - Holanda, Gervina Brady Moreira (2023)
Universities face bureaucratic challenges that impact their administrative procedures and decision-making. To overcome these barriers, it is essential to streamline public services without compromising their quality. An effective approach to achieve this goal is the adoption of Business Process Management (BPM), which enables the monitoring and adaptation of procedures. Additionally, strategies such as the use of Plain Language and Visual Rights can make communication more transparent and accessible to users. At the Federal University of Ceará (UFC), the high dropout rate among students results in the availability of remaining vacancies through a unified notice for Transfer from other Higher Education Institutions and Admission of Graduates. However, some applications are rejected due to a lack of understanding of the information presented. With this in mind, this research aimed to enhance the communication and understanding of notices by applying BPM, Plain Language, and Visual Rights techniques to improve the process of selecting remaining vacancies at UFC and create a new version of the notice, with an emphasis on simplifying the language and improving comprehension. The study adopted a qualitative approach, involving the analysis of existing documents and literature to identify guidelines and best practices for plain language writing of notices, as well as the use of simple language process mapping techniques. The research also assessed how users perceive the understanding of the language used in UFC notices. Based on the responses obtained, guidelines were established for creating the new version of the notice to address comprehension issues. As a result, the notice was rewritten using best practices of plain language, visual rights, and process modeling to enhance communication within the institution.